PENGUKURAN TINGKAT KUALITAS PRODUKSI D21N INNER LENS - Susanti, Dewi; Fajrah, Nofriani (LPPM Universitas Putera Batam, 2021)
The technology competition in the industry today is very tight. Companies that maintain product quality and improve product quality according to customer requirements. Therefore, in the production process the Reflector and Inner Lens experience several obstacles that often occur in the production process, namely defects in the bubble, silver, and white dot. This study aims to identify the disabilities that often occur if well controlled, to determine the causes of these disabilities. Fishbone diagrams are used to identify factors that cause defects. There are 4 factors that cause defects based on the fishbone diagram, namely human, machine, environmental and material factors. The results showed that there was no data out of control. The dominant defect types in the D21N Inner Lens product are bubbles (53.5%) and the 760 Reflector A product is silver (69.7%).